The reality of feminization of the audiovisual media in Algeria Empirical study on Annaba local radio - بولوداني سهام (International Journal of Social Communication, 2022)
This study deals with the problem of feminization, constantly progressing, of the profession of journalism, a problem that is located in a vision of gender and in studies of morphology of the profession of journalism. It aims to probe the impacts of feminization on editorial activities in the local radio of Annaba, by practicing a questionnaire for all female journalists on the radio. The study demonstrated the presence of feminine touch in the realization of journalistic missions at Annaba radio.